Dicoma anomala Enhances Phthalocyanine Mediated Photodynamic Therapy in MCF-7 Breast Cancer Cells - Chota, Alexander; George, Blassan P.; Abrahamse, Heidi (Frontiers in Pharmacology, 2022)
Breast cancer is one of the most common types of cancer in women, and it is regarded as the second leading cause of cancer-related deaths worldwide. The present study investigated phytochemical profiling, in vitro anticancer effects of Dicoma anomala methanol root extract and its enhancing effects in phthalocyanine mediated PDT on MCF-7 (ATCC® HTB-22TM) breast cancer cells. Ultra-high performance liquid chromatography coupled to electrospray ionization quadrupole-time of flight mass spectrometry (UHPLC-qTOF-MS2) was used to identify the secondary metabolites in the crude extract. The 50% inhibitory concentration (IC50) of the two experimental models was established from dose response studies 24 h post-treatment with D. anomala methanol root extract (25, 50, and 100 μg/mL) and ZnPcS4 (5, 10, 20, 40, and 60 μM) mediated PDT. The inverted microscope was used to analyze morphological changes, trypan blue exclusion assay for viability, and Annexin V-fluorescein isothiocyanate (FITC)-propidium iodide (PI) for cell death mechanisms. Immunofluorescence analysis was used to investigate the qualitative expression of the Bax, p53, and caspase 3 apoptotic proteins. Experiments were performed 4 times (n=4) and SPSS version 27 software was used to analyze statistical significances. D. anomala methanol root extract induced cell death in MCF-7 cells by decreasing cell viability. The combination of D. anomala methanol root extract and ZnPcS4 mediated PDT led to a significant increase in apoptotic activities, expression of Bax, and p53 with significant decrease in cell viability. These findings pinpoint the possibility of D. anomala methanol root extract of being employed as a natural antiproliferative agent in the treatment of various cancers.